Impact of a targeted bundle of audit with tailored education and an intubation checklist to improve airway management in the emergency department: an integrated time series analysis. Issue 9 (17th June 2020) - Groombridge, Christopher; Maini, Amit; Olaussen, Alexander; Kim, Yen; Fitzgerald, Mark; Mitra, Biswadev; Smit, De Villiers
Abstract : Background: Endotracheal intubation (ETI) is a commonly performed but potentially high-risk procedure in the emergency department (ED). Requiring more than one attempt at intubation has been shown to increase adverse events and interventions improving first-attempt success rate should be identified to make ETI in the ED safer. We introduced and examined the effect of a targeted bundle of airway initiatives on first-attempt success and adverse events associated with ETI. Methods: This prospective, interventional cohort study was conducted over a 2-year period at an Australian Major Trauma Centre. An online airway registry was established at the inception of the study to collect information related to all intubations. After 6 months, we introduced a bundle of initiatives including monthly audit, monthly airway management education and an airway management checklist. A time series analysis model was used to compare standard practice (ie, first 6 months) to the postintervention period. Results: There were 526 patients, 369 in the intervention group and 157 in the preintervention comparator group. A total of 573 intubation attempts were performed. There was a significant improvement in first-attempt success rates between preintervention and postintervention groups (88.5% vs 94.6%, relative risk 1.07; 95% CI 1.00 to 1.14, p=0.014). After the introduction of the intervention the first-attempt success rate increased significantly, by 13.4% (p=0.006) in the first month, followed by a significant increase in the monthly trend (relative to the preintervention trend) of 1.71% (p<0.001). The rate of adverse events were similar preintervention and postintervention (hypoxia 8.3% vs 8.9% (p=0.81); hypotension 8.3% vs 7.0% (p=0.62); any complication 27.4% vs 23.6% (p=0.35)). Conclusions: This bundle of airway management initiatives was associated with significant improvement in the first-attempt success rate of ETI. The introduction of a regular education programme based on the audit of a dedicated airway registry, combined with a periprocedure checklist is a worthwhile ED quality improvement initiative.